2017
DOI: 10.1177/0898010117697863
|View full text |Cite
|
Sign up to set email alerts
|

“Making the Ordinary More Extraordinary”: Exploring Creativity as a Health Promotion Practice Among Older Adults in a Community-Based Professionally Taught Arts Program

Abstract: Results suggest that professionally taught arts programming can contribute to well-being and may contribute to brain health through promoting an enhanced ability to focus. Holistic nursing treats creativity as healing, and results suggest that creative engagement should be a priority in therapeutic programming, and individual counseling for older adults to begin engaging in some form of art making suited to their abilities should be incorporated into nursing practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
4
16
0
1
Order By: Relevance
“…Participants utilized various art supplies that were provided, which helped to enhance their ability for creativity. Findings such as these are common among other art studies such as Cantu and Fleuriet ( 41 ), which showed that art creation in art programs can promote well-being.…”
Section: Discussionsupporting
confidence: 73%
“…Participants utilized various art supplies that were provided, which helped to enhance their ability for creativity. Findings such as these are common among other art studies such as Cantu and Fleuriet ( 41 ), which showed that art creation in art programs can promote well-being.…”
Section: Discussionsupporting
confidence: 73%
“…For example, one of the participants was enrolled in a regular creative writing class; another one of the participants was deeply in touch with spiritual practices. The value of active engagement in creative practices has been associated with improved attention, social well-being and a sense of calmness in other disciplines (Cantu & Fleuriet, 2018), and SLPs may benefit from such engagement as well.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing wealth of evidence supports the positive contribution and impact of creative art, there is no consensus on what aspects are deemed important to older adults (Arts Council for Wales, 2018). Furthermore, there is limited knowledge about how their participation in community create arts impact their lives (Cantu and Fleuriet, 2017; Clift, 2012). McAvinchey (2013) states participation in creative arts amongst older adults is one of the most substantial, emerging and under researched area.…”
Section: Literature Reviewmentioning
confidence: 99%